Voltage Reversal During the Operation of a Sediment Bioelectrochemical System Intergrated in a Brackish Aquaculture Model: Causes and Solutions to Overcome - Nhung, Tran Hong; Phuong, Vu Ha; Hai, Pham The (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3DO - 10.25073/2588-1140/vnunst.5308, 2021)
The bioelectrochemical system (SBES) is expected to become a novel alternative energy source with numerous outstanding potentials. Nevertheless, there are a few challenges that need to be overcome before it can be applied in practice. One of those problems is the voltage decreases or voltage reversals of the system. The control of voltage reversal will be crucial for long-term operation of SBES. In this study, we studied the effects of different environmental factors such as light, temperature and air humidity and of internal SBES factors such as sulfate concentration, dissolved oxygen concentration and biofilm formation on voltage reversal in the SBES. Light, temperatute and air humidity did not appear to be associated to voltage reversal. On the other hand, the change in dissolved oxygen (DO) concentration and biofilm formation on the cathode appeared to be the major factors causing such phenomenon. Therefore, aeration and frequent replacements of the cathode are suggested to overcome the problem, which will help to enhance the practical applicability of the SBES.